Imposition of Criminal Sanctions for Narcotics Abuse Below the Minimum Limit - Jennifer Maiyola Situmorang; Hatarto Pakpahan (Jurnal Cakrawala Hukum, 2023)
This study aims to examine the legal process of narcotics abuse in Indonesia. The impact of excessive use of narcotics results in central nervous, psychological/psychic damage, and the most fatal is death. The problem in this study examines the development of the narcotics abuse trial process in Indonesia so that it can suppress many cases of narcotics abuse. Cases of drug abuse are often found with sentences below the minimum limit. This study uses normative legal research methods with several approaches, namely the statutory approach and the conceptual approach. Based on the results of these data, this study shows that judges are contrary to the Narcotics Law with an objective minimum standard for violations that endanger society and the state. The judge who examines and adjudicates the case has misapplied the law because he has imposed a sentence with the threat of certain minimum sanctions as stipulated in the laws and regulations. This creates uncertainty in law enforcement which is regulated in the law as it should.